Praktik Penempatan Mahasiswa Jurusan Teknik Mesin Fakultas Teknik Universitas Riau Di Dalam Pelaksanaan Kerja Praktik - Handika Iqbal Pratama; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Practical Work is mostly done by the final students as their graduation requirements which arerequired by the university, as well as students of the Mechanical Engineering Department at UniversitasRiau. Law No. 44 of 2015 concerning the Delivery of Work Accident Guarantees and Death Assurance hasobliged that each Practical Worker participant must receive work safety guarantees from the company, butin reality students often do not get the rights they should get.This legal writing aims to find out the implementation of practical work programs in legalprotection, guarantee of their rights by law, protection of their work safety, and the obstacles experiencedby participants of the Practical Work (students, companies, and the Department of Mechanical Engineering,Universitas Riau) in implementing practical work, as well as the solutions to overcome the obstacles.The writing of this study used a juridical empirical approach to see the identification andeffectiveness of law in reality through attitudes, actions and opinions in real terms, by conducting directresearch in the field regarding the implementation of the placement of practical work participants in theDepartment of Mechanical Engineering, Universitas Riau. While the population and sample were all partiesrelated to the problems examined in this study. The data sources used were primary, secondary, and tertiarydata. Data collection techniques in this study were carried out by observation, interviews and literaturereviews.From the research findings on the problem, there are two main things that can be concluded. First,legal protection for Practical Work students at Universitas Riau based on Law Number 44 of 2015concerning the Delivery of Work Accidents and Death Collateral was not fulfilled by the companies wherethey carried out the Practical Work. Second, the agreement process of several parties carried out by thecompany (PT. PLN Pekanbaru Generation Sector) for participants of the practical work at UniversitasRiau's Mechanical Engineering Department is contrary to the applicable law, making this agreement nulland void. Some recommendations from the author, first, the government should pay more attention to thelegal protection of the rights of participants in practical work and more closely monitor the practical workimplementations as well as make good standard procedures. The government should also provideinformation to companies and universities that carry out practical work. Secondly, agreements in practicalwork need to be mandatory and legal rules that regulate like the agreement on "apprentice" participantsshould be formulated to ensure the rights and more balanced positions of participants in practical work. Thecontents of the agreement must fulfill and guarantee the rights of participants in practical work, this isbecause their position in this agreement is very weak.